Design and Modeling of Fixture for Cylinder Liner Honing Operation (Global Journals of Research in Engineering, 2013)
Model of new fixture design is presented for cylinder liners honing operation to improve productivity and reduce the rejection rate on honing machine. In mass production of cylinder liners, the industrial honing involves abrasive finishing process, during that liners need to be fixed on honing machine, For that a new model of fixture setup relative to honing operation of cylinder liner is proposed, planned and modeled such that the liners can be held in form closure and totally immobilized. This paper uses newer and innovative design of present day manufacturing industries for locating, positioning, clamping, for uniforce clamping hydraulic clampings are used. Fixture design is one of the important factor that play a role in providing manufacturing processes with more productivity and have brought many benefits like reduced rejection. Fixtures are used in many manufacturing processes to locate, hold and support the work securely. While designing this paper, a good number of literature written on the subject by renowned authors are referred. The paper includes finished parts model and 3D assembled view of fixture using Pro/Engineer Wildfire.
Keywords: honing fixture; cylinder liners; fixture planning and fixture assembly